The Extraction THE EXTRACTION OF SANDALWOOD OIL USING THE MICROWAVE HYDRODISTILLATION METHOD WITH VARIATION OF MASS AND MATERIAL TREATMENT: THE EXTRACTION OF SANDALWOOD OIL USING THE MICROWAVE HYDRODISTILLATION METHOD WITH VARIATION OF MASS AND MATERIAL TREATMENT - Mohammad Istnaeny Hudha, Istnaeny (jurnal ATMOSPHERE, 2021)
The extraction of sandalwood oil using the microwave hydrodistillation method can be another alternative in the process of extracting sandalwood to obtain and improve the quality of the sandalwood oil produced. This research aims to determine the appropriate formula from the mass variation of the material and the treatment of sandalwood powder in obtaining high yield and good oil quality. The method of making sandalwood oil used is the Microwave Hydrodistillation method. From the results of this reseacrh, the best yield calculation results in the variation of the mass of 200 grams of material with dry wind treatment. Based on the density test, the result is 0.98 and the acid number is 0.6732.